2019
DOI: 10.1186/s12957-018-1550-z
|View full text |Cite
|
Sign up to set email alerts
|

Improved survival among oral cancer patients: findings from a retrospective study at a tertiary care cancer centre in rural Kerala, India

Abstract: BackgroundOral cancer is very common in India. The reported 5-year survival of such patients is around 50% after treatment with surgery and radiotherapy, much lower than most of the developed countries.MethodsA retrospective study of a prospective database of oral cancer patients undergoing surgery from June 2009 to June 2013 was conducted. Follow-up details were updated from case records and by phone calls. Data were double entered in EpiData Entry version 3.1 and were analysed using EpiData Analysis software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 18 publications
(5 reference statements)
4
38
1
Order By: Relevance
“…These results are consistent with those of recent studies that have analyzed other cancer databases [17,18]. Moreover, the cure rate of oral cancer was significantly higher in high-SDI countries than in other countries [19,20]. The present study demonstrated that, with the same ASRI, the ASRM and age-standardized DALYs of oral cancer patients in developed countries or regions were generally lower than those in developing countries.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with those of recent studies that have analyzed other cancer databases [17,18]. Moreover, the cure rate of oral cancer was significantly higher in high-SDI countries than in other countries [19,20]. The present study demonstrated that, with the same ASRI, the ASRM and age-standardized DALYs of oral cancer patients in developed countries or regions were generally lower than those in developing countries.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, surgery, radiation therapy, and chemotherapy are the standard primary treatments for oral cancer. Despite the advent of multidisciplinary approaches, the prognosis of advanced stage oral cancer patients is still poor, and the overall survival rate within five years remains at around 30–50% [ 9 ], mainly due to the high tendency for local recurrence, treatment resistance, and thereafter regional lymph node metastasis. At present, visual screening combined with tissue biopsy is the most common screening approach for oral cancer, but this may provide insufficient information, which results in under-diagnosis and improper care [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 It has been reported that the overall 5-year survival rate is only 50% with possibilities of recurrence. 8,9 The global prevalence of OSCC is highlighted in Malaysia, with a 1.5% increase in oral cancer incidence and mortality rates of 1.2% as reported by GLOBOCAN in 2018. 4 The risk factors that are associated with OSCC include tobacco smoking, heavy alcohol consumption, poor oral hygiene, unhealthy diet and microbial infection.…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma (OSCC) has been classified as the most common type of oral cancer, accounting for greater than 90% of malignancies originating from the oral cavity 7 . It has been reported that the overall 5‐year survival rate is only 50% with possibilities of recurrence 8,9 . The global prevalence of OSCC is highlighted in Malaysia, with a 1.5% increase in oral cancer incidence and mortality rates of 1.2% as reported by GLOBOCAN in 2018 4 .…”
Section: Introductionmentioning
confidence: 99%